Yeasts from sub-Antarctic region: biodiversity, enzymatic activities and their potential as oleaginous microorganisms - Martinez, A.; Cavello, Ivana Alejandra; Garmendia, G.; Rufo, C.; Cavalitto, Sebastian Fernando; Vero, S. (Extremophiles)
Various microbial groups are well known to produce a range of extracellular enzymes and other secondary metabolites. However, the occurrence and importance of investment in such activities have received relatively limited attention in studies of Antarctic soil microbiota. Sixty-one yeasts strains were isolated from King George Island, Antarctica which were characterized physiologically and identified at the molecular level using the D1/D2 region of rDNA. Fifty-eight yeasts (belonging to the genera Cryptococcus, Leucosporidiella, Rhodotorula, Guehomyces, Candida, Metschnikowia and Debaryomyces) were screened for extracellular amylolytic, proteolytic, esterasic, pectinolytic, inulolytic xylanolytic and cellulolytic activities at low and moderate temperatures. Esterase activity was the most common enzymatic activity expressed by the yeast isolates regardless the assay temperature and inulinase was the second most common enzymatic activity. No cellulolytic activity was detected. One yeast identified as Guehomyces pullulans (8E) showed significant activity across six of seven enzymes types tested. Twenty-eight yeast isolates were classified as oleaginous, being the isolate 8E the strain that accumulated the highest levels of saponifiable lipids (42 %). Fil: Martinez, A. Universidad de la República. Facultad de Química; Uruguay Fil: Cavello, Ivana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Fermentaciones Industriales. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Fermentaciones Industriales; Argentina Fil: Garmendia, G. Universidad de la República. Facultad de Química; Uruguay Fil: Rufo, C. Universidad de la República. Facultad de Química; Uruguay Fil: Cavalitto, Sebastian Fernando. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en ...